Clinical implications of skeletal muscle blood-oxygenation-level-dependent (BOLD) MRI - Partovi, Sasan; Jacobi, Björn; Müller-Eschner, Matthias (Magnetic resonance materials in physics, biology and medicine, 2012)
Blood-oxygenation-level-dependent (BOLD) contrast in magnetic resonance (MR) imaging of skeletal muscle mainly depends on changes of oxygen saturation in the microcirculation. In recent years, an increasing number of studies have evaluated the clinical relevance of skeletal muscle BOLD MR imaging in vascular diseases, such as peripheral arterial occlusive disease, diabetes mellitus, and chronic compartment syndrome. BOLD imaging combines the advantages of MR imaging, i.e., high spatial resolution, no exposure to ionizing radiation, with functional information of local microvascular perfusion. Due to intrinsic contrast provoked via changes in hemoglobin oxygen saturation, it is a safe and easy applicable procedure on standard whole-body MR devices. Therefore, BOLD MR imaging of skeletal muscle is a potential new diagnostic tool in the clinical evaluation of vascular, inflammatory, and muscular pathologies. Our review focuses on the current evidence concerning the use of BOLD MR imaging of skeletal muscle under pathological conditions and highlights ways for future clinical and scientific applications.
Published online: 29 February 2012
Gesehen am 26.06.2018